PERBEDAAN PENGARUH PEMBERIAN TOPIKAL EKSTRAK DAUN BAKAU (Bruguiera gymnorrhiza) DAN GEL BIOPLACENTON PADA MAKROSKOPIS KULIT TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR Sprague dawley DENGAN LUKA SAYAT - Akib, Salsabila Nadhifa; Kurniawaty, Evi (Medula, 2023)
Wound is loss of continuity from tissue’s anatomical structure which can be caused by pathological process from within or outside body. Wound healing process consists of four stages, namely haemostasis, inflammation, proliferation, and maturation. Bruguiera gymnorrhiza mangrove plant is a type of mangrove that is rich in bioactive compounds. Bruguiera gymnorrhiza leaf extract has bioactive compounds that can work as antibacterial, anti-inflammatory, analgesic and proliferative agents which affect wound healing process. This research is pure experimental with post test only control group design. Sample consisted of 30 rats divided into 3 groups. K-: 0,2 cc topical aquades, K +: 0,2 cc topical bioplacenton gel, P1: Bruguiera gymnorrhiza leaf extract 80% in 14 days of observation. Observation data were recorded in observation sheet and analyzed statistically. The results showed that topical extract of Bruguiera gymnorrhiza leaves 80% affected macroscopic wound healing in form of wound length’s reduction to 0.17 cm on 14th day but Kruskal-wallis test showed no significant macroscopic difference in wound healing (p > 0.05) between K-, K +, and P1. Topical extract of Bruguiera gymnorrhiza leaves 80% affected macroscopic wound healing in form of wound length’s reduction but there was no significant difference in incision wound healing macroscopically between K-, K +, and P1 at dose 0.2 cc / day.